Gene transfer into tobacco plant (Nicotiana tabacum L.) mediated by Agrobacterium tumefaciens - Dung, Tran Thi; Ho, Nguyen Huu (Academia Journal of Biology, 2015)
The transfer of foreign genes into high plants mediated by Agrobacterium tumefaciens is a standard technique in plant molecular biology and genetic engineering. Leaf discs of the tobacco cultivar K326 were co-cultivated with Agrobacterium tumefaciens strain EHA 105 harbouring the plasmid plTB2 containing cryIA(c), bar and gus A genes. Infected leaves were transferred onto the MS (Murashige & Skoog) medium supplemented with 5-30 mg/l PPT (phosphinothricin) for selection of the transformants. PPT resistant shoots have been obtained and they also expressed the gus activity. The presence of the Bt toxin gene from Bacillus thuringiensis was shown by PCR (polymerase chain reaction).